CODE – MIXING IN ENGLISH CLASSES OF SMPN 14 KOTA BENGKULU: VIEWS FROM THE TEACHERS - Tri Ramadhaniarti; Safnil Arsyad; Arono Arono (JOALL (Journal of Applied Linguistics and Literature), 2017)
English teachers in all levels of education in Indonesia try hard to make their students able to speak and write English. Teachers sometimes  use code-mixing in their  classroom  instructions. This study is conducted to investigate Code – Mixing in English Classes of SMPN 14 Kota Bengkulu: Views From the Teachers. The participants were the English teachers who teach English at SMPN 14 Kota Bengkulu. The data were collected  from  audio-recording and interviewing to the teachers. The results indicated that teachers used  inter-sentential code-mixing  more frequently than intra-sentential code-mixing. It also found  that all of the teachers used code-mixing in pre-activity, while activity and post-activity of teaching and learning process in their English classes. They also used code-mixing for  giving instruction, translation and asking for clarification.   The English-Indonesian pattern is the most frequently used by the teachers in teaching English. The teachers used code-mixing in teaching English in the English classes to make the students able to understand the purpose of teaching and learning process easily.